Efficacy and safety of primary suture following laparoscopic common bile duct exploration in the treatment of elderly patients with cholecystolithiasis complicated by choledocholithiasis - Li, Huixing; Duan, Xuhong; Wu, Zhenyu (Frontiers in Surgery, 2025)
Background and aimThe study aimed to evaluate the efficacy and safety of primary suture following laparoscopic common bile duct exploration (LCBDE) in the treatment of elderly patients with cholecystolithiasis complicated by choledocholithiasis.MethodsWe retrospectively reviewed 164 elderly patients, aged older than 70 years, who underwent laparoscopic cholecystectomy (LC) and laparoscopic common bile duct exploration at our center from January 2015 to December 2024. The patients were categorized into two groups according to the surgical strategy used, namely, primary suture following LC + LCBDE (PS group) and T-tube drainage following LC + LCBDE (T-tube group). General data, intraoperative and postoperative outcomes, and postoperative complications in the two groups were compared and analyzed.ResultsThere were no significant differences in age (77.1 ± 4.6 vs. 78.3 ± 5.2 years, p = 0.126), gender (p = 0.523), body mass index (24.7 ± 2.1 vs. 24.3 ± 1.8, p = 0.192), diameter of common bile duct (14.1 ± 3.8 vs. 13.4 ± 2.5 mm, p = 0.158), American Society of Anesthesiologists risk grading (p = 0.545), and hematological indicators and comorbidities (p > 0.05) between the two groups. All the patients successfully underwent laparoscopic surgery without any case being converted to laparotomy. There was no significant difference in intraoperative blood loss between the PS and T-tube groups (54.6 ± 26.4 vs. 58.8 ± 24.7 mL, p = 0.297). However, surgical duration (113.7 ± 23.8 vs. 129.2 ± 39.5 min, p = 0.004) was significantly shorter in the PS group. In addition, the PS group had a significantly shorter exhaustion time (2.1 ± 0.7 vs. 2.9 ± 0.6 days, p = 0.000) and postoperative hospital stay (6.1 ± 1.9 vs. 8.2 ± 1.6 days, p = 0.000) and lower hospitalization expenses (21.2 ± 5.9 vs. 26.6 ± 7.4 thousand, p = 0.000). In terms of postoperative complications, there were significant differences in the incidences of electrolyte disturbance (11.3% vs. 23.7%, p = 0.042) and bile leakage (0.0% vs. 8.6%, p = 0.030) between the PS and T-tube groups. No serious complications, such as intra-abdominal infection, bleeding, or death, occurred in either group.ConclusionPrimary suture following LCBDE is a safe and effective treatment approach for cholecystolithiasis combined with choledocholithiasis in elderly patients. When the surgical criteria are strictly executed, primary suture offers superior perioperative outcomes over T-tube drainage, facilitating patients’ recovery without increasing postoperative complications.